A multidisciplinary approach to the engineering of footwear cushioning: A practical example of gym training shoes - Morio, Y. M. M.; Bouten, L.; Duraffourg, S.; Delattre, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
According to sports goers, one of the most important features of gym training shoes is their cushioning properties. The optimal amount of cushioning is, however, complex to define. In the present paper, a multi-disciplinary approach was proposed to investigate and determine the optimal perceived midsole cushioning for gym training shoes. Firstly, impact tests were performed to characterise a wide range of shoes representing the gym training shoe market. Trained sensory panel method and mechanical testing were combined to determine the relationship between the perception of cushioning and the shoe`s mechanical properties. Secondly, the preferred cushioning perception was assessed. Then, numerous midsole configurations were tested using finite element method (FEM) to determine the combinations with the best cushioning properties in order to reduce the number of physical prototypes. To assess the best configuration estimated by the numerical model, a wear test was performed as a final validation. From this approach, relationship between the mechanical properties of the midsole and perception of cushioning was found, and an optimal perceived cushioning was identified. Moreover, through FEM numerical simulations, a great number of midsole configurations and designs were tested without making any actual prototypes. Prototype shoes were based on the best numerical solution. The final wear test confirmed that the prototype gym training shoes achieved the preferred perception of cushioning. The present methodology proposes a framework, which empowers the use of athlete`s and exerciser`s perception in shoe design.